Measuring Risk-adjusted Customer Lifetime Value and its Impact on Relationship Marketing Strategies and Shareholder Value - Ryals, Lynette; Knox, Simon (Emerald Group Publishing Limited, 2005)
The calculations which underlie efforts to balance marketing spending on customer acquisition and customer retention are usually based on either single- period customer profitability or forecasts of customer lifetime value (CLTV). This paper argues instead for risk-adjusted CLTV, which is termed the economic value (EV) of a customer, as the means for marketing to assess both customer profitability and shareholder value gains.
Keywords: Customers; Relationship marketing; Shareholders; Value analysis